Interaction of inter- and intralaminar damage in scaled quasi-static indentation tests: Part 2 – Numerical simulation. (February 2016) - Sun, X.C.; Wisnom, M.R.; Hallett, S.R.
Abstract: A numerical study, accompanied by the experimental data from Part 1 of this paper, provides a clear picture of the global damage behaviour and local response of four scaled Carbon Fibre Reinforced Polymer (CFRP) laminates under quasi-static transverse loading. Interface elements with a cohesive formulation are employed to model delamination, matrix cracks and their interaction. The predictive damage from different numerical simulations with different levels of detail is presented, and the validity is illustrated both qualitatively and quantitatively. Specifically the number of inserted potential intralaminar crack paths is varied from no cracks, through single, then double, to multiple cracks. It is shown that the models with the capability to simulate multiple matrix cracks best predict the key aspects of barely visible damage of composite laminate during quasi-static loading.